Higher Education Teaching Philosophy: An Academia Research Syllabus Approach (Global Journal of Human-Social Science, 2025)
The study aims to provide a comprehensive literature framework about the subject it addresses. It uses this approach to develop and put forward a based subject curriculum setting for academic research-doing classrooms. The syllabus is the guideline that, bests distinguish the teaching highperforming management at university level. It is a written prospect that underlines information about academic courses, or classes, yet leading to define expectations and responsibilities. It thus becomes a model designed to develop students professional thinking and writing. The study relies on the educational principles stated in the Experiential Learning Theory (ELT) to underline the need for universities to look at the updating of their postgraduate curriculums design and preparation from these educational perspectives: the First is, students' Google search engines academic research-doing reliance. And the Second is, research academic teaching courses-based Flipped Learning. The study has used a qualitative approach to investigate the subject presented. This criterion included the collection and analysis of academic and scientific materials such as papers, books, and Internet-accredited websites. The result of this study is intended to benefit the academic and scientific community, respectively.
Keywords: academic research-doing; google search engines; advanced research skilled-knowledge foundation; academic research-doing curriculum approach I